Kajian Keandalan Air Sungai Cisadane Memenuhi Laju Permintaan Air Baku PDAM Kota Bogor - Arwin Arwin; Yuniria Mukmin (Journal of Regional and City Planning, 2006)
The river Cisadane is the only potential raw water source to fulfil the demand rate of the Local Water Supply Enterprice (PDAM) Bogor of 1225 L/sec (2005). Due to the impact of population growth and city expansion, the need for raw water increases up to 2375 L/sec (2010). The rate of additional demand for raw water source to a total of 1200 L/sec (2010), such that an increase of 3 x 600 L/sec is needed at the Ciherang-Pondoh Intake. The existing Ciherang-Pondoh Intake was approved (SIPA) by the authority to increase tapping from 600 L/sec up to 1200 L/sec, and the World Bank approved a fast track project to increase the mentioned capacity. The Cisadane river debit as well as the extreme water debit (1969-1999) during the dry seasons are random variables. The reliability of the Cisadane river debit during the dry seasons was determined statistically, proceeded by a theoretical distribution test against the measured dry seasons data (Chow, 1964). A data array was made, then the goodness of fit of the data was tested to find the conformity between samples and the theoretical distribution function, which represent the actual debit phenomena (Normal Distribution, log-normal, Gumbel and log-pearson III). Further on, the reliabity curve of the Cisadane raw water source was constructed to assure supply to the PDAM, and fulfil the design criteria. In case that the river debit can not fulfil the demand for the multisector (domestic, irigation, and down stream industry) raw water source, then a further study need to be conducted to develop the Cisadane water source using a dam.Keywords: Rate of water demand, goodness-of-fit, reliability curve, Water-source Criteria